2009
DOI: 10.1016/j.neuron.2009.09.027
|View full text |Cite
|
Sign up to set email alerts
|

DSCAM and DSCAML1 Function in Self-Avoidance in Multiple Cell Types in the Developing Mouse Retina

Abstract: DSCAM and DSCAM-LIKE1 (DSCAML1) serve diverse neurodevelopmental functions, including axon guidance, synaptic adhesion, and self-avoidance, depending on the species, cell type, and gene family member studied. We examined the function of DSCAM and DSCAML1 in the developing mouse retina. In addition to a subset of amacrine cells, Dscam was expressed in most retinal ganglion cells (RGCs). RGCs had fasciculated dendrites and clumped cell bodies in Dscam−/− mice, suggesting a role in self-avoidance. Dscaml1 was exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
304
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(325 citation statements)
references
References 48 publications
21
304
0
Order By: Relevance
“…Although the mammalian DSCAM gene is unable to generate such wide molecular diversity, it has been demonstrated to mediate homophilic repulsion, promoting dendrite self-avoidance in the developing mouse retina (Fuerst et al, 2008(Fuerst et al, , 2009. Moreover, roles of DSCAM in both de novo and learning-related synaptogenesis have been shown using diverse biological models (Yamagata and Sanes, 2008;Li et al, 2009), and the interaction of DSCAM with PSD-95 and MAGI scaffolding proteins seems to be necessary for its synaptic function (Yamagata and Sanes, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mammalian DSCAM gene is unable to generate such wide molecular diversity, it has been demonstrated to mediate homophilic repulsion, promoting dendrite self-avoidance in the developing mouse retina (Fuerst et al, 2008(Fuerst et al, , 2009. Moreover, roles of DSCAM in both de novo and learning-related synaptogenesis have been shown using diverse biological models (Yamagata and Sanes, 2008;Li et al, 2009), and the interaction of DSCAM with PSD-95 and MAGI scaffolding proteins seems to be necessary for its synaptic function (Yamagata and Sanes, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…DSCAM has been recently shown to be involved in dendrite morphogenesis in mouse retina (Fuerst et al, 2008(Fuerst et al, , 2009. To assess the impact of DSCAM overexpression on dendrite morphology of hippocampal neurons, we decided to transfect DIV7 neurons with a plasmid encoding DSCAM-IRES-GFP (Yamagata and Sanes, 2008), and to analyze the dendritic phenotype 2 d later (DIV7 ϩ 2).…”
Section: Dscam Overexpression In Hippocampal Neurons Inhibits Dendritmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kirrel3 may regulate the self-avoidance of subsets of axons, by masking intrinsic adhesion proteins, so that they can disperse into multiple smaller glomeruli in the AOB. The transmembrane molecules DSCAM and DSCAML1 have been proposed to promote self-avoidance through such a mechanism in the mouse retina (Fuerst et al, 2009). …”
Section: Establishment Of a Functional Glomerular Map In The Aobmentioning
confidence: 99%
“…While the vertebrate DSCAM gene does not encode multiple isoforms, it shares functional similarities to fly Dscam. In DSCAM deficient mice, retinal ganglion cells have defects in neuronal spacing and dendritic arborization patterns exhibiting neuronal self-avoidance phenotypes (35,36). In contrast, studies in the chicken retina have shown that DSCAM plays a role in synapse formation by promoting the targeting of retinal ganglion cell dendrites and bipolar cell axons to the same layer (37).…”
mentioning
confidence: 99%